Distance edge coloring and collision‐free communication in wireless sensor networks. Issue 1 (7th January 2013) - Drira, Kaouther; Seba, Hamida; Effantin, Brice; Kheddouci, Hamamache
Abstract Motivated by the problem of link scheduling in wireless sensor networks where different sensors have different transmission and interference ranges and may be mobile, we study the problem of "distance edge coloring" of graphs, which is a generalization of proper edge coloring. Let Gbe a graph modeling a sensor network. An ℓ‐distance edge coloring of Gis a coloring of the edges of Gsuch that any two edges within distance ℓof each other are assigned different colors. The parameter ℓis chosen, so that the links corresponding to two edges that are assigned the same color do not interfere. We investigate the ℓ‐distance edge coloring problem on several families of graphs that can be used as topologies in sensor deployment. We focus on determining the minimum number of colors needed and optimal coloring algorithms. © 2013 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq 2013